PENERAPAN METODE POS-TO-POS UNTUK MENINGKATKAN KEAKTIFAN MURID DALAM PEMBELAJARAN IPS - Mazdha Khirani, Nailyviatul; Bachri, Syamsul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to optimize students’ kinesthetic intelligence through the Pos-to-Pos method to increase student activeness in Social Studies (IPS) learning, focusing on financial literacy and community empowerment. The gap between the dominantly kinesthetic learning style of junior high school students and the theoretical demands of IPS content, combined with the reliance on conventional lecturing, has resulted in low physical, verbal, mental, and emotional activeness. The Pos-to-Pos method adapts the tactical procedure of Scout activities into four learning posts: Pasar Transaksi (financial institution role play), Sandi Prioritas (budget and priority-scale management), Aksi Pemberdayaan (community problem-solving project), and Juru Hitung and Refleksi (concept puzzle and self-reflection). This research used a Pre-Experimental One-Group Pretest-Posttest Design involving 32 seventh-grade students with a dominant kinesthetic learning profile. Data were collected through a multiple-choice cognitive test and an observation rubric of student activeness. The average learning activity score increased significantly from 52.34 (quite active) to 78.56 (active), with a t-value of 15.23 (p < 0.01). Posttest results showed that 60% of students successfully achieved the high activity category. The highest increase occurred in the physical dimension (N-gain = 0.72) and the emotional dimension (N-gain = 0.68). Observation data also indicated a marked increase in physical, verbal, mental, and emotional engagement across the four posts. It is concluded that the Pos-to-Pos method is effective in optimizing kinesthetic intelligence and increasing student activeness in IPS learning.